The Effect of Monosodium Glutamate on Estradiol Levels in Pregnant Rats - Amelya Permata Sari; Rika Susanti (Institute of Computer Science (IOCS), 2021)
Monosodium glutamate (MSG) is a form of the glutamic acid salt. The purpose of this study to analyze the effect of MSG on estrogen levels in pregnant rats. This research is an experimental study was conducted at January in the Biomedical Laboratory of the Faculty of Medicine, Andalas University, Padang. Total of samples consist of 18 pregnant Wistar rats which were divided into three groups, namely control, treatment one and treatment two. Blood sampling and surgery were performed on day 20 to assess male estrogen levels. Estrogen levels were measured by using the One Way ANOVA. There were significant differences on serum estrogen levels between the control group and treatment group one (p = 0.012) and treatment two (p <0.01) and between treatment group one and treatment group two (p <0.001).The conclusion, there is an effect of MSG on estrogen levels in pregnant rats.